2012
DOI: 10.5435/jaaos-20-07-423
|View full text |Cite
|
Sign up to set email alerts
|

Management of Humeral Shaft Fractures

Abstract: Humeral shaft fractures account for approximately 3% of all fractures. Nonsurgical management of humeral shaft fractures with functional bracing gained popularity in the 1970s, and this method is arguably the standard of care for these fractures. Still, surgical management is indicated in certain situations, including polytraumatic injuries, open fractures, vascular injury, ipsilateral articular fractures, floating elbow injuries, and fractures that fail nonsurgical management. Surgical options include externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
107
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 42 publications
0
107
1
5
Order By: Relevance
“…It has been postulated that earlier surgical intervention with ORIF leads to earlier recovery of radial nerve palsy [21,22]. Nevertheless, a relatively high incidence of secondary radial nerve palsy is associated with ORIF [19]. Still the question of correlation of bone union and recovery of radial nerve palsy remains unclear [14,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been postulated that earlier surgical intervention with ORIF leads to earlier recovery of radial nerve palsy [21,22]. Nevertheless, a relatively high incidence of secondary radial nerve palsy is associated with ORIF [19]. Still the question of correlation of bone union and recovery of radial nerve palsy remains unclear [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Both, ORIF and IN are well-established procedures with high rates of 85-93 % of recovery following primary radial nerve palsy [12,[17][18][19][20][21]. In the case of acute primary radial nerve palsy open reduction facilitates fracture treatment and enables simultaneous exploration of the radial nerve to determine the extent and the type of lesion [1,7,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of diaphyseal fracture of humerus using titanium elastic nail and at the end of the study the authors concluded that the titanium elastic nails offer a number of potential advantage over traditional way of treating long bone fracture including early immobilization, shorter hospital stay and less risk of loss of fracture position [16]. In two comparative studies treating closed diaphyseal fractures humerus with elastic nail and plate osteosynthesis, the authors concluded that elastic stable nail is applicable for routine use in appropriate selected humerus shaft fracture [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] As is widely known, the most common injury associated with closed diaphyseal humeral fracture is the concomitant injury of the radial nerve. [3] The recent literature has suggested that closed fractures are frequently associated with neuropraxia of the radial nerve with spontaneous recovery expected in more than 80% of cases.…”
mentioning
confidence: 99%